Molecular Basis of Wrinkled Variants Isolated From Pseudoalteromonas lipolytica Biofilms - Zeng, Zhenshun; Lin, Shituan; Li, Qian; Wang, Weiquan; Wang, Yuqi; Xiao, Tangfu; Guo, Yuexue (Frontiers in Microbiology, 2022)
Many Pseudoalteromonas species are dominant biofilm-forming Gammaproteobacteria in the ocean. The formation of Pseudoalteromonas biofilms is often accompanied by the occurrence of variants with different colony morphologies that may exhibit increased marine antifouling or anticorrosion activities. However, the genetic basis of the occurrence of these variants remains largely unexplored. In this study, we identified that wrinkled variants of P. lipolytica mainly arose due to mutations in the AT00_08765, a wspF-like gene, that are associated with decreased swimming motility and increased cellulose production. Moreover, we found that the spontaneous mutation in flhA, encoding a flagellar biosynthesis protein, also caused a wrinkled colony morphology that is associated with cellulose overproduction, indicating that flhA plays a dual role in controlling flagellar assembly and polysaccharide production in P. lipolytica. Investigation of wrinkled variants harboring spontaneous mutation in dgcB, encoding a GGDEF domain protein, also demonstrated dgcB plays an important role in regulating cellulose production and swimming motility. In addition, by screening the suppressor of the AT00_08765 variant strain, we also identified that the spontaneous mutation in cheR and bcsC directly abolished the wrinkled phenotype of the AT00_08765 variant strain, suggesting that the chemosensory signaling transduction and cellulose production are crucial for the determination of the wrinkled phenotype in P. lipolytica. Taken together, this study provides insights into the genetic variation within biofilms of P. lipolytica.